2016
DOI: 10.1111/jan.13183
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Competence Scale: a systematic and psychometric review

Abstract: The value of Nurse Competence Scale has been confirmed in determining relationships between background variables and competence. The instrument has been widely used with experienced and newly graduated nurses and their managers. Cross-cultural validation must be continued using rigorous methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
164
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(175 citation statements)
references
References 89 publications
7
164
0
4
Order By: Relevance
“…Work experience, and its impact on the confidence of EMS professionals, was often cited as a factor that influenced the conveyance decision. Research on registered nurses in hospitals has similarly demonstrated a positive link between work experience and competence, and showed this had an influence on patient outcomes 82. Higher education levels, permanent employment and participation in educational programmes also boosted employees’ feelings of competence 82.…”
Section: Discussionmentioning
confidence: 97%
“…Work experience, and its impact on the confidence of EMS professionals, was often cited as a factor that influenced the conveyance decision. Research on registered nurses in hospitals has similarly demonstrated a positive link between work experience and competence, and showed this had an influence on patient outcomes 82. Higher education levels, permanent employment and participation in educational programmes also boosted employees’ feelings of competence 82.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported on research into the testing of a tool's validity and reliability implementing such a tool for clinically based assessment (e.g., Liou and Cheng [16] ) and integrative reviews of the literature on nursing competency standards (recenlty, e.g., Robb et al; [1] Chiarella et al; [17] Yanhua and Watson; [18] Halcomb et al; [19] Flinkman et al [7] ).…”
Section: Review Of the Relevent Literaturementioning
confidence: 99%
“…[6] Competence has been recognized as a core component of professional standards. [7] It is an effective application of knowledge and skills. Performance is clearly concerned with demonstrated ability to do something, a method of measuring achievement of competency.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 The adaptationof instruments for the evaluation of subjective constructs,for different languages and cultures, has also been the subject of a large number of investigations, including discussions on the appropriate methodological process to ensure that the instrument preserves its properties of validity and reliability after adaptation. 1 In the last decade, this type of research has produced a considerable number of nursing researches, [9][10][11][12][13] reflecting the concern of these professionals to identify the most appropriate measurement instrument for a given situation or condition, considering the one that addresses the monitoring of patients in clinical practice and that contemplates the perception of the individuals themselves in the evaluation of their state of health. 14 From the analysis of the increase in measurement instruments available in the scientific literature, the authors identified two important aspects to be overcome: the need to identify the available questionnaires for a specific use in the various subjects, so that they may be known to interested professionals and the need to know the measures that would be considered more appropriate (valid and reliable) among the various available instruments.…”
Section: Introductionmentioning
confidence: 99%